Implementation of Endurance Training Model Based on Basic Soccer Techniques to Soccer Coaches in Pariaman City - Ridho Bahtra; Aldo Naza Putra; Andri Gemaini (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
Soccer is a game sport that requires good endurance skills. Good endurance will help players to be able to play optimally during the game. The selection of the right training model will encourage the creation of a structured and directed training process. Based on the results of interviews and observations in the field, there are findings that trainers still use the old or conventional training model. Lack of knowledge of trainers about training models can ultimately lead to the inability of trainers to create varied training programs. To overcome these problems, football coaches need to be given various training models. The approach methods used in solving partner problems are 1) Workshops in order to improve the understanding of trainers in preparing training programs, 2) Field practice to understand more deeply how to implement Drill-Based Endurance training models and 3) Follow-up discussions in the context of monitoring and evaluation. The result of this activity is an increase in the trainer's understanding and ability in training to increase endurance abilities.